Comprehensive analysis of the NAC transcription factor gene family in Sophora tonkinensis Gagnep - Ximei Liang; Shuangshuang Qin; Guili Wei; Xiaoyun Guo; Shugen Wei; Fan Wei; Ying Liang (BMC Plant Biology)
Abstract Background Sophora tonkinensis Gagnep. has long been utilized in the treatment of anti-inflammatory and pain-relieving, with its principal active compounds being alkaloids and flavonoids. NAC transcription factors, a large family of plant-specific regulators, play pivotal roles in growth, development, stress responses, and secondary metabolism. However, comprehensive genome-wide characterization of S. tonkinensis NAC gene family (StNAC) remains unexplored. Results This study identified 85 NAC proteins from the S. tonkinensis genome database. Phylogenetic analysis revealed that StNAC proteins were categorized into 15 subgroups based on their homology with Arabidopsis thaliana NAC proteins. Gene structure analysis demonstrated a variation in intron numbers ranging from 1 to 7, with a majority of StNAC genes containing 2–3 introns. Chromosomal distribution analysis indicated an uneven spread of StNAC genes across 9 chromosomes, with the highest number of StNAC genes on Chr3. Detection of 4 tandem duplicates and 32 segmental duplicates revealed that segmental duplication primarily drive StNAC genes amplification. Prediction of cis-regulatory elements suggested the involvement of StNAC genes in growth, stress responses, and hormone regulation. Gene expression analysis showed substantial variability expression of StNAC genes across different tissues. Notably, eight StNAC genes were identified as significantly associated alkaloid and flavonoid levels. qRT-PCR validation indicated that five genes were highly expressed in tissues, corroborating transcriptome data. Conclusion These findings offer valuable insights for further functional characterization of NAC genes and their potential roles in alkaloid and flavonoid biosynthesis in S. tonkinensis.